MODERNIZATION OF EVALUATION OF BANKING ACTIVITIES IN THE CONDITIONS OF THE DIGITAL ECONOMY - Ekaterina Butenko; Sabiyat Magomedsaidova (Вестник Северо-Кавказского федерального университета, 2022)
The work proves the urgency of developing new methods for assessing the development of e-commerce as uch, in the context of the banking sector in particular, due to the active growth ofprofits in the Internet sector, the гт growth in the number of IT companies and their introduction into the banking sector, which will later change the face of the modern bank and approaches to its management. The processes of globalization, which in recent decades have been actively influencing all spheres of society: sociocultural, political, spiritual, certainly affect the economic sphere, including, and to a greater extent, therefore, the issue considered in the work is relevant at the moment.